Stock Valuation Analysis of Digital Company PT Indoternet TBK (EDGE) Using The Discounted Cash Flow Method - Litha Fara R; Mardani Supranata (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid development of Indonesia’s digital infrastructure has driven significant growth in data center services, positioning PT Indointernet Tbk (EDGE) as one of the key industry players. However, this growth has been accompanied by substantial capital expenditures that may affect the company’s long-term financial stability, creating a need to evaluate whether its rising market valuation is supported by fundamental performance. The objective of this study is to determine the intrinsic value of EDGE’s stock in 2023 using the Discounted Cash Flow (DCF) method and to assess its alignment with the company’s market price. This research employs a quantitative approach with a descriptive analysis method to provide an objective and systematic valuation based on historical financial data and projected future cash flows. Secondary data were collected from EDGE’s 2021–2023 annual reports, publications from the Indonesia Stock Exchange (IDX), and relevant academic literature. The analysis includes compiling key financial components such as EBIT, taxes, CapEx, and changes in working capital, calculating Free Cash Flow (FCF), determining the Weighted Average Cost of Capital (WACC), estimating Terminal Value (TV), and computing intrinsic value through discounted cash flows. The findings reveal strong EBIT growth of 55% in 2021–2022 and 40% in 2022–2023, yet a sharp decline in FCF due to increased CapEx for the EDGE 2 data center. With a WACC of 12.61% and a negative terminal value of –33,736,050.88, the resulting intrinsic stock value of –Rp8.18 indicates that EDGE’s fundamentals do not support its 2023 market price of Rp5,100.